Toroidal versus Fano Resonances in High Q planar THz Metamaterials - Gupta, Manoj (2017)
Radiative losses are crucial in optimizing the performance of metamaterial-based devices across the electromagnetic spectrum. Introducing structural asymmetry in meta-atom design leads to the excitation of sharp Fano resonances with reduced radiative losses. However, at larger asymmetries, the Fano resonance becomes highly radiative which results in the broadening of the asymmetric line shaped resonances. Here, the authors experimentally demonstrate a scheme to couple mirrored asymmetric Fano resonators through interaction of anti-aligned magnetic dipoles which results in a strong toroidal resonance in 2D planar metasurface. The quality (Q) factor and the figure of merit of the toroidal dipolar mode are significantly higher than the Fano resonance. Moreover, the authors discover that the exponential decay of the Q factor of toroidal resonance mode occurs at half the rate of that in the Fano resonance as the asymmetry of the system is enhanced which indicates significant tailoring and the suppression of the radiative loss channel in the toroidal configuration. The weakly radiative toroidal resonance in planar metamaterials offers the potential for applications in terahertz and optical sensing, spectroscopy, narrow-band filtering, and large modulation.